Green Synthesis of Lactone‐Based Conjugated Polymers for n‐Type Organic Electrochemical Transistors. (2nd January 2022) - Wang, Yazhou; Zeglio, Erica; Wang, Lewen; Cong, Shengyu; Zhu, Genming; Liao, Hailiang; Duan, Jiayao; Zhou, Yecheng; Li, Zhengke; Mawad, Damia; Herland, Anna; Yue, Wan; et al.
Abstract: As new and better materials are implemented for organic electrochemical transistors (OECTs), it becomes increasingly important to adopt more economic and environmentally friendly synthesis pathways with respect to conventional transition‐metal‐catalyzed polymerizations. Herein, a series of novel n‐type donor–acceptor‐conjugated polymers based on glycolated lactone and bis‐isatin units are reported. All the polymers are synthesized via green and metal‐free aldol polymerization. The strong electron‐deficient lactone‐building blocks provide low‐lying lowest unoccupied molecular orbital (LUMO) and the rigid backbone needed for efficient electron mobility up to 0.07 cm 2 V −1 s −1 . Instead, polar atoms in the backbone and ethylene glycol side chains contribute to the ionic conductivity. The resulting OECTs exhibit a normalized maximum transconductance g m, norm of 0.8 S cm −1 and a μC * of 6.7 F cm −1 V −1 s −1 . Data on the microstructure show that such device performance originates from a unique porous morphology together with a highly disordered amorphous microstructure, leading to efficient ion‐to‐electron coupling. Overall, the design strategy provides an inexpensive and metal‐free polymerization route for high‐performing n‐type OECTs. Abstract : Lactone building blocks are incorporated into the backbone of donor–acceptor (D–A) copolymers to combine a sustainable polymerization strategy with the high performance needed for n‐type organic electrochemical transistors (OECTs). All the polymers are synthesized via aldol polycondensation. Among them, p(C‐T)‐based OECT achieves a µ C * of 6.7 F cm −1 V −1 s −1 and a normalized maximum transconductance gm, norm of 0.8 S cm −1 .